In Vitro Uptake of Labelled Amino Acids by the Skin of Children with Generalized Congenital Analgesia - Merzel, J.; Blumen, G.; Schmidt, B. J.; Maia, J. C.; Raw, I.; Castro, N. M. (Nuklearmedizin - NuclearMedicine, 1969)
The “in vitro” uptake of labelled tyrosine, tryptophan and leucine by the skin of two children with GCA (Generalized Congenital Analgesia) was compared with that in normal (white and negro) individuals. Through radioactivity counts and radioautographic procedures it was shown that the uptake of the two aromatic amino acids was reduced in the GCA individuals the protein synthesis seemed to be normal.The possible relationship of these results to an abnormal metabolite isolated from the urine of these patients is discussed.